Use of testosterone replacement therapy in the rehabilitation of patients with intensive care unit-associated weakness and hospital-associated deconditioning: the Singapore General Hospital rehabilitation experience - Samuel, Geoffrey Sithamparapillai; Swee, Du Soon (Singapore medical journal, 2024)
Abstract Introduction: Rehabilitation medicine in a tertiary care hospital involves attending to many patients affected by intensive care unit (ICU)-associated weakness (ICU-AW) and hospital-associated deconditioning (HAD). These conditions contribute to poor long-term functional outcomes and increased mortality. We explored the role of short-term adjunctive androgen therapy in this group of patients in improving the rehabilitative outcomes. Methods: This was a retrospective analysis of five patients with either ICU-AW or HAD who were given testosterone replacement therapy (TRT) or oxandrolone for a total of 2 weeks during the period from April to November 2020 was undertaken. During the 2-week trial period, the subjects underwent standard rehabilitation therapy. Results: Grip strength was used as the primary outcome measure, and the mean improvement was 4.2 kg (+24.9%), which is encouraging in a 2-week timeframe. This was matched with good functional recovery in terms of distance ambulated and less assistance needed for ambulation. Sex hormone analysis was also done before initiation of TRT, and it showed that four out of five of the subjects were biochemically hypogonadal. None of the subjects dropped out or experienced any significant adverse events over the 2-week trial period. All the subjects except one improved to full independence at 3 months post-discharge. Conclusion: TRT has the potential to be used as a useful adjunct to standard rehabilitation in enhancing functional recovery in critically ill patients. A multidisciplinary approach would ensure that suitable patients benefit from optimal nutrition, optimal rehabilitation and synergistic testosterone therapy in a clinically sound and resource-efficient fashion.